Small vs. Large Unruptured Cerebral Aneurysm: Concerns With the Age of Patient - Zheng, Jianfeng; Xu, Ru; Sun, Xiaochuan; Zhang, Xiaodong (Frontiers in Neurology, 2021)
Objective: The coiling and clipping of unruptured cerebral aneurysms (UCAs) in older patients has increased rapidly, and aneurysm size was a significant factor for decision-making in the treatment of UCAs. The purpose of the study was to investigate the impact of age on the functional outcomes of patients between the small versus large UCAs. Methods: We conducted a retrospective study for consecutive cases of UCAs admitted from May 2011 to December 2020. According to the maximum diameter of UCA, patients were divided into small UCAs (≤ 5 mm) group and large UCAs (>5 mm) group. Baseline characteristics, clinical complications, and outcomes of patients between the two groups were analyzed. Results: A total of 564 UCA patients received preventive treatment, including 165 small UCAs and 399 large UCAs. Compared with the small UCA group, the incidence of ischemia event in the large UCA group was significantly higher (7.3 vs. 2.4%; p = 0.029). Multivariable analysis demonstrating age (p = 0.006) and treatment modality (p < 0.001) were independent risk factors associated with poor outcome for patients with large UCAs. Conclusions: Preventive treatment of small UCAs is safe and effective, but older patients with large UCAs are at high risk of poor outcome, and the operations should be more cautious.